Creatively Gifted Students are not like Other Gifted Students
XII, 264 p.
Keywords: This book focuses on the needs of creatively gifted students and how schools can meet those needs. Creatively gifted students show exceptional levels of creativity. These students may or may not have developed other talents and abilities, yet. Even when their abilities and talents are apparent, the needs of creatively gifted students may not be recognized by current gifted education programs. Regardless of whether a creatively gifted student is included in these programs, schools often inadvertently ignore their special needs. The goal of this book is to share the newest research about the attributes and needs of creatively gifted students and the kinds of programs that best address those special needs. The overarching goal of this book is to share with scholars, educators, and practitioners the latest research on creatively gifted students and the kinds of programs that best meet the unique needs of these students. Through the knowledge and experiences shared here, we hope to help close the gap between what these children need and what they are getting.